Early and Sustained Reduction in Donor-Specific Antibodies in Desensitized Living Donor Kidney Transplant Recipients: A 3-Year Prospective Study. Issue 2 (February 2016) - Shaffer, David; Feurer, Irene D.; Crowe, Deborah; Schaefer, Heidi
Abstract : Background: Desensitization with IVIG and rituximab allows acceptable graft survival in sensitized kidney transplant recipients with preexisting donor-specific antibodies (DSAs) and a positive crossmatch. There is little published data reporting the durability of DSA removal in kidney transplant recipients treated with IVIG and rituximab. Methods: We conducted a 3-year prospective DSA monitoring study in living donor kidney recipients with preexisting DSA to assess the durability of DSA removal after a perioperative protocol of IVIG and rituximab. All recipients had flow crossmatch titers less than 1:32. Data were analyzed using linear mixed effects models and Kaplan-Meier survival methods. Results: The longitudinal database comprised 210 mean fluorescence intensity (MFI) determinations. Forty-two DSAs were identified in 29 patients. Pretreatment MFI averaged 4715 ± 3962 (range, 947-20 129). At 1 month posttransplant, 18 patients (62%) had a complete response (MFI < 1000) and an additional 9 patients (31%) had a partial response (MFI reduced but >1000). There was a 46% reduction ( P < 0.001) in DSA MFI at 1 month posttransplant that was sustained throughout the 3-year follow-up period and was observed for both class I and II DSAs regardless of pretreatment MFI levels. With a mean posttransplant follow-up of 1048 ± 574 days, 3-year patient and graft survivals were 95% and 90%. Four patients (14%) had acute rejection between days 125 and 560. Conclusions: Desensitization with IVIG and rituximab results in early and sustained DSA removal over a 3-year posttransplant period in living donor kidney transplant recipients with pretransplant DSA and a positive crossmatch, excellent patient and graft survivals and a low incidence of acute rejection.